Faktor Faktor Yang Mempengaruhi Persetujuan Pembiayaan Petani Kelapa Sawit Di Bank Syariah Mandiri - Putri Dian Sari Damanik; Sri Fajar Ayu; Iskandarini Iskandarini (Universitas Medan Area, 2021)
The role of financial institutions is very much needed in the form of supporting the development of the oil palm agricultural sector. Banking is one of the agents of development. The main function of banking is as a financial intermediary institution. Therefore, banks are expected to be able to channel financing to the agricultural sector. However, in the distribution of credit or financing facilities, there are terms and elements of credit that must be fulfilled by farmers as prospective debtors at Bank Mandiri Syariah, after which a feasibility analysis will be carried out on prospective debtors. The purpose of this study was to analyze the effect of financing needs, income, collateral value, education, and length of farming on financing approval for oil palm farmers. The method of determining the sample was carried out by using a census, namely the entire debtor in which the farmers who applied for oil palm financing were sampled in this study as many as 61 people. In this study, it was processed using logistic regression analysis. The results showed the variables of financing needs and collateral have a significant effect on financing approval, while income, education and length of farming variables have no significant effect on financing approval. If the variables of financing needs, income, collateral, education and length of farming increases, the financing approval will increase/agree.Keywords: Palm oil; Farmers; Financing; Banking.